Uncertainty and expectations in Portugal's tourism activities: Impacts of COVID-19 - Norberto Santos; Claudete Carla Oliveira Moreira (Research in Globalization, 2021)
Portugal has established itself as one of the most competitive tourist destinations in the world. The tourist destination, which comprises the mainland territory and two archipelagos, enjoyed unprecedented, sustained growth in tourist activity in 2019. The COVID-19 pandemic has had serious repercussions on the national tourism system, although government measures have been implemented to mitigate the impacts. The results for tourist accommodation show that after the first phase of the pandemic there was a slight recovery of some tourism activity indicators, mainly in more consolidated destinations: Algarve and Madeira. The low-density territories with peri-urban and rural features, very much leaning towards nature tourism (Alentejo and Central Portugal) suffered a less severe impact on tourism demand, and domestic tourism was able to mitigate some negative effects. The data is organized using year-on-year variation, considering the years 2019 and 2020. The conclusions seek to make proposals for the recovery of post-COVID-19 tourism and define some of the ways forward.
Keywords: 330; Tourism destination; Tourism competitiveness; Destination management; Crisis management; Destination image; COVID-19 impacts